Fine particle removal from flue gas using emulsion liquid membrane technique. Issue 3 (May 2019) - Ren, Xiaxia; Li, Hongxia; Liu, Ce; Zhao, Mingyu; Zhang, Junjie
Abstract: A novel method for removing fine particle from flue gas by using a water in oil (W/O/W) type emulsion liquid membrane (ELM) is presented. The ELM is composed of L-113A or Span 80 serve as surfactant, kerosene as diluent, and water serve as external phase and internal phase, respectively. An L9 (34) orthogonal test is used to obtain optimum experimental conditions. The result shown that the optimum operating condition for the ELM system are as follows: L-113A serve as the surfactant with concentration of 4% (v/v), stirring speed for emulsion preparing (R) is 4500rpm, internal phase to organic phase (Rio) is 5:5 (v/v) and volume ratio of W/O emulsion phase to external phase (Reo) is 1:4 (v/v), at which the removal efficiency of fine particle from flue gas by ELM system can reach 98%.